A visão tácita e explícita da modelagem - Rezende, Juliana Ribeiro de (2012)
This research aims to analyze the explicit and tacit knowledge in the department of applied patternmaking in an clothing industry, together with reviews of literature and professional experience to demonstrate the importance of this technology in the design of new products and as a means to innovate. The methodology has been colleting information on patternmaking department of a clothing industry, on-site observation, data collection, through the use of questionnaires in order to perform comparisons of knowledge studied in the Higher Education Institution with the modellers industries of Londrina / PR and collection development based on knowledge of the patternmaking technique or moulage dimensional and flat, as tools for innovation in the forms and the use of textile material. The collection will follow the trends of summer 2013, with an aesthetic or The Sporting Life Sport Contemporary style and ephemeral and concepts and how the speed and Futurism.